2022
DOI: 10.1108/cdi-11-2021-0288
|View full text |Cite
|
Sign up to set email alerts
|

Academic independent directors in China: factors influencing career decision-making

Abstract: PurposeThe board independence norm has shaped corporate governance globally, but research on the supply of independent directors (IDs) is limited. “New careers” studies suggest that dynamic non-conventional career paths are evolving, but empirical evidence is mostly limited to Western societies. The authors studied reasons for academics to consider taking on an ID role in firms in China.Design/methodology/approachEmploying a quantitative methodology, data were collected via a survey targeting 1,500 academics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 106 publications
(219 reference statements)
0
1
0
Order By: Relevance
“…In reality, good academic grades are required for good jobs such as medical doctor, computer science, engineering, etc. Furthermore, other research has shown that academic achievement has an impact on students' career choices (Kocak et al, 2021;Lu et al, 2022;Osuizugbo et al, 2022;Ulas-Kilic et al, 2020). The present study tends to find out that academic performance has a relationship with career decisionmaking.…”
Section: The Effect Of Academic Reason On Career Decisionmentioning
confidence: 52%
“…In reality, good academic grades are required for good jobs such as medical doctor, computer science, engineering, etc. Furthermore, other research has shown that academic achievement has an impact on students' career choices (Kocak et al, 2021;Lu et al, 2022;Osuizugbo et al, 2022;Ulas-Kilic et al, 2020). The present study tends to find out that academic performance has a relationship with career decisionmaking.…”
Section: The Effect Of Academic Reason On Career Decisionmentioning
confidence: 52%